Tunable Bandgaps in Layered Structure Magnonic Crystal-Ferroelectric - Morozova, Maria A.; Grishin, Sergey V.; Sadovnikov, Alexandr V.; Romanenko, Dmitrii V.; Sharaevskii, Yurii P.; Nikitov, Sergey A. (IEEE transactions on magnetics, 2015)
The spectral characteristics of the hybrid spin-electromagnetic waves in multiferroic layered structure magnonic crystal (MC)-ferroelectric were theoretically and experimentally investigated. The main features of the bandgaps formation in such a structure were compared with the case of a single MC. The possibility of the bandgap characteristics control with varying electric field is demonstrated.